2004
DOI: 10.1016/j.ymthe.2004.05.004
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Nonviral Method for Delivering Genes and siRNAs to Skeletal Muscle of Mammalian Limbs

Abstract: Delivery is increasingly being recognized as the critical hurdle holding back the tremendous promise of nucleic acid-based therapies that include gene therapy and more recently siRNA-based therapeutics. While numerous candidate genes (and siRNA sequences) with therapeutic potential have been identified, their utility has not yet been realized because of inefficient and/or unsafe delivery technologies. We now describe an intravascular, nonviral methodology that enables efficient and repeatable delivery of nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
173
1
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(178 citation statements)
references
References 39 publications
3
173
1
1
Order By: Relevance
“…Our results are consistent with previous reports by Wolff's group where effective nuclear transgene was observed in muscle near the injection site [20].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Our results are consistent with previous reports by Wolff's group where effective nuclear transgene was observed in muscle near the injection site [20].…”
Section: Discussionsupporting
confidence: 94%
“…This technique was first reported by Liu's group and Wollf's group in 1999, where effective nuclear transgene expression in hepatocytes in mice was achieved by hydrodynamic tail vein injection. In 2004, Wolff's group showed that the rapid injection of large volumes of naked pDNA into the great saphenous vein of the distal hind limb of a rat (HLV injection) resulted in effective nuclear transgene expression in skeletal muscle [20]. Based on previous great reports, we attempted to achieve mitochondrial delivery of pDNA targeted to skeletal muscle using HLV injection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[10][11][12] Moreover, recombinant adeno-associated viral (rAAV) vectors and naked plasmid are two different gene transfer systems used for IM delivery in animal models [13][14][15][16][17] and in humans. 18,19 Recently, regional vascular infusion of a vector to achieve skeletal muscle transduction has been reported for plasmid DNA (pDNA) 20,21 and for rAAV vectors. 8,22 Among the rAAV serotypes analyzed to date, rAAV1 and rAAV8 are among the most efficient for muscle transduction.…”
Section: Introductionmentioning
confidence: 99%